New insight into recombination and thermalization in As2Se3 - Ristein, Jürgen; et al. (Journal of Non-Crystalline Solids, 1987)
Simultaneous studies of photoluminescence and photoconductance in high electric fields reveal that emission of light occurs in single crystals of As2Se3 by geminate pair recombination only. After rapid thermalization excited carriers form free excitons which within a few picoseconds become self-trapped. The detailed picture which evolves for recombination in crystals, however, apparently does not apply to the glass. © 1987.
UnivIS-Import:2015-03-05:Pub.1987.nat.dphy.IAP.exphys.newins